RHEUMATOID ARTHRITIS CAUSES, DIAGNOSIS AND PERIODS - Khasanov Farrukh Sheralievich; Son of Koldoshev Feruzjon Zahid (Web of Journals Publishing, 2024)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune inflammatory disease of connective tissues, which occurs mainly in the form of erosive-destructive polyarthritis with an exacerbation of perivertebral joints.
Keywords: Rheumatoid arthritis RA, inflammation, pain, autoimmune inflammation, ESR.